A student solved an equation, as shown below.

1 * (8 - 12x) =x-2(2x+1

2-3x=x-4x+2

7 - 3x = - 3x + 2

2=2

Based on the student's work, complete the statement below.

Use the drop-down menus to make the statement below true.

The student solved the equation

because the original equation has



2-3x+3x-3x+3x+2

Correctly,incorrectly

No solution, one solution, infinitely many solutions

1 answer

The student solved the equation incorrectly because the original equation has no solution.
Similar Questions
  1. A student solved an equation, as shown1/4 (8 - 12x) = x -2(2x+1) 2 - 3x = x - 4x + 2 2 - 3x = -3x + 2 2 - 3x + 3x = -3x + 3x + 2
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. A student solved an equation, as shown below1/4(8-12x) =x-2(2x+1) 2-3x = x-4x+2 2-3x=-3x+2 2-3x+3x = -3x+3x+2 2=2 Based on the
    1. answers icon 1 answer
  3. A student solved the following equation using the following steps:2(2x + 2) = 4(x + 4) 4x + 4 = 4x + 4 4 = 4 Infinite solutions
    1. answers icon 1 answer
more similar questions